Football Management Systems And The Impact On Team Performance - Mwiikisa, Lineker (Digital Repository of Theses, 2025)
This thesis explores the relationship between football management systems and team performance in the Zambia Premier League (ZPL). Football management systems encompass various aspects such as governance, financial management, talent development, and stakeholder engagement, all of which play a crucial role in determining the success and competitiveness of football clubs. The ZPL, as the highest tier of football in Zambia, faces unique challenges, including limited funding, inadequate infrastructure, and poor governance, which hinder the effective performance of its teams. Through a comprehensive analysis of existing management practices and their impact on team performance, this study aims to identify the factors that contribute to the success or failure of football clubs within the league. The research focuses on the 2023/2024 season of the ZPL, examining selected clubs to assess the effectiveness of their management systems and the challenges they face. By applying key theories such as the Resource-Based View (RBV) and Stakeholder Theory, the study provides a deeper understanding of how resource allocation, governance structures, and stakeholder engagement influence on-field success. The findings of this thesis will offer valuable insights to club managers, policymakers, and stakeholders, suggesting ways to enhance management practices and improve overall team performance. Ultimately, the research aims to contribute to the broader field of sports management in developing countries, providing practical recommendations for the sustainable growth of football in Zambia.